Модифікування керамічної цегли та будівельного розчину зовнішніх стін будівель та споруд для підвищення їх експлуатаційної надійності - Семенів, Роксолана Михайлівна (Національний університет "Львівська політехніка", 2019)
Дисертаційна робота присвячена питанням розроблення теоретичних основ підвищення експлуатаційної надійності зовнішніх стін будівель і споруд шляхом модифікування поверхні керамічної лицьової цегли високоефективними нано-рідинами та застосування будівельного розчину на основі модифікованого низькоемісійного багатокомпонентного цементу для мурування МС 22,5, що забезпечує технічні, екологічні та економічні переваги. Оптимізовано склади високоефективних нано-рідин з використанням нано-Аl2О3, що забезпечують високий рівень гідрофобізації цегляної кладки із зменшенням показників водопоглинання, капілярного підтягування та підвищенням атмосферо- і морозостійкості без утворення тріщин. Розроблено модифіковані багатокомпонентні цементи для мурування з пониженим клінкер-фактором (40 %), які дозволяють одержати легковкладальні розчинові суміші, що забезпечують якість цегляної кладки – повнота і рівномірність заповнення швів, дотримання їх раціональної товщини, адгезію розчину, а також міцність, морозостійкість, деформативність і стійкість до висолоутворення зовнішніх стін будівель і споруд. Диссертация посвящена разработке теоретических основ повышения эксплуатационной надежности наружных стен зданий и сооружений путем модифицирования поверхности керамического лицевого кирпича высокоэффективными нано-жидкостями и применения строительного раствора на основе модифицированного низкоэмиссионного многокомпонентного цемента для кладки МС 22,5, что обеспечивает технические, экологические и экономические преимущества. Оптимизированы составы высокоэффективных нано-жидкостей с использованием нано-Аl2О3, что обеспечивают высокий уровень гидрофобизации кирпичной кладки с уменьшением показателей водопоглощения, капиллярного подтягивания и повышением атмосферо- и морозостойкости без образования трещин. Разработаны модифицированные многокомпонентные цементы для кладки с пониженным клинкер-фактором (40 %), которые позволяют получить растворные смеси, что обеспечивает качество кирпичной кладки – полнота заполнения швов, соблюдение их рациональной толщины, а также морозостойкость, деформативность и устойчивость к высолообразованию наружных стен зданий и сооружений. The dissertation is devoted to questions of increasing the operational reliability of external walls of buildings and structures. This is achieved by modification of ceramic brick surface by hydrophobic substances of new generation and building mortar on the basis of a low-emission masonry cement with additives of air-tightening action. An analytical review of literary sources devoted to the current state of problems of brick external walls of buildings and structures is made. The questions connected with principles of modification of ceramic brick and building mortar are considered, as well as theoretical preconditions of research are determined. The characteristics of the materials and the main methods of research used in the work are described. The results of development and research of physical and mechanical properties of modified ceramic bricks and building mortars are presented. The phase composition and microstructure of the efflorescences from ceramic facing brick and the building mortar were obtained. It is investigated the influence of nano-liquid on the brick properties using the method of orthogonal central composite planning. It has been determined that the most effective hydrophobic substance is modifier containing nano-Al2O3 powder. It is established that during surface treatment by nano-liquid (amount of nano-Al2O3 – 0,8 %) water absorption decreases to 1.2–1.6 %, capillary suction – to 0.08–0.12 kg/m2∙hour0,5. The electron microscopy method confirmed that the modification of the ceramic brick surface by the hydrophobizing nano- liquids makes it possible to compact the structure through the colmatation of pores and microcracks, which reduces the capillary suction of the ceramic facing brick. It also results an atmospheric resistance and frost resistance of the ceramic facing brick. Experimental studies have confirmed that a significant influence on the properties of brick masonry has a binder and building mortar on its basis. Use of low-emission masonry cement MС 22.5 with a reduced clinker factor (40 %), as binder, leads to an increase of salt efflorescence resistant of the brick masonry. Due to modification, a fine-pore microstructure of a cement matrix of building mortar is formed, which impede the process of material destruction. It was established that for mortar mixtures based on МС 22.5, obtained modified building mortars of the design grade for compressive strength М100, which are characterized by increased frost resistance (F75) and atmospheric resistance. It was shown that during the investigation of brick masonry using modified building mortar and ceramic facing brick with nano-liquid, the adhesion strength was 0.73 MPa, the compressive strength – 8.5 MPa. At the same time, the use of a modified mortar based on low-emission masonry cement MC 22.5 and a modified ceramic facing brick by nano-liquid ensures efflorescences resistance of brick masonry. Nano-liquid was used to protect the surface of brick fencing structures during repairing work. The production of an industrial batch of masonry cement with air-tightening additive EN 413-1 MC 22.5 in the amount of 70 tons was produced at PJSC "Ivano-Frankivsk Cement". During the laying of external walls of low-rise residential development LTD "Pidgaetska building company" was used masonry cement MC 22.5 EN 413-1 in the quantity of 70 tons; economic efficiency is 154.62 UAH per 1 m3 of mortar.
Модификация керамического кирпича и строительного раствора наружных стен зданий и сооружений для повышения их эксплуатационной надежности
Modification of ceramic brick and building mortar for external walls of buildings and structures to increase their operational reliability
Keywords: керамічна лицьова цегла; поверхневе модифікування; нано-рідина; модифікований багатокомпонентний цемент для мурування; будівельний розчин; кладка; керамический лицевой кирпич; поверхностное модифицирование; нано-жидкость; модифицированный многокомпонентный цемент для кладки; строительный раствор; кладка; ceramic facing brick; surface modification; nano-liquids; modified multicomponent cement for masonry; building mortar; masonry; 691.421:691.535